Comparability of financial statements in large emerging economies after adoption of IFRS : the case of Russia and Brazil - Dolgikh, Tatiana; Procházka, David, 1979 říjen 10.-; Mejzlík, Ladislav, 1961-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2022)
The thesis examines whether the application of International Financial Reporting Standards (IFRS) by large emerging economies such as Russia and Brazil has contributed to an increase in the comparability of financial statements, both within and outside the given national economy. The data for emerging countries examined in the study were matched against a developed economy (namely Canada) as a benchmark and example that emerging economies attempts to match. The first chapter presents background information on the development of the Russian and Brazilian accounting systems, describes their current status and compares local accounting standards of Russia and Brazil with IFRS standards. The second chapter contains a literature review of previous studies dedicated to IFRS adoption and the level of financial statement comparability. The third chapter explains the research design based on two major approaches on how to measure the level of comparability of financial statements. The fourth chapter presents and discusses the results of an empirical analysis utilizing a sample of 21 companies listed on stock exchange markets of all three countries.
Vedoucí práce: David Procházka
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor disert. práce]; disertace; dissertations